Conservation at Stake: Institutionalized Environmentalisms and Indigenous Knowledges About How to Protect the Brazilian Atlantic Forest - Thomaz Sandroni, Laila (Ethnobiology Letters, 2023)
This paper aims to compare two different sets of solutions on best pathways for biodiversity conservation present in a specific territory in the Brazilian Atlantic Forest, in southern Bahia. We look specifically at three interconnected administrative instances: the Tupinambá de Olivença Indigenous Land; the Una Biological Reserve; and the Una Wildlife Refuge. We show that different perspectives regarding what it means to preserve nature come into focus in this territory. These are intertwined with power relations that highlight the inequality in the legitimacy of different groups in decision making for environmental governance. We map the causes and solutions for biodiversity degradation proposed by two contrasting narratives: the Indigenous perspective and the institutionalized western science-based environmentalism developed by state agencies and non-governmental organizations that work with conservation projects in the region. We expect to equalize these contrasting perspectives that are commonly seen in hierarchical terms. We conclude by advocating for managing combinations of diverse sets of knowledge and for pluralism in conservation efforts that accounts for underlying power relations.